Clinical, laboratory and immune aspects of Zika virus-associated encephalitis in children. (January 2020) - Salgado, Doris M.; Vega, Rocío; Rodríguez, Jairo Antonio; Niño, Ángela; Rodríguez, Rocío; Ortiz, Ángela; DeLaura, Isabel; Bosch, Irene; Narváez, Carlos F.
Highlights: Zika virus (ZIKV) infection was detected in an important fraction of pediatric encephalitis cases. ZIKV encephalitis patients displayed a higher frequency of exanthema and shorter duration of hospitalization compared to patients with encephalitis caused by other etiological agents. Cerebrospinal fluid analysis shown a remarkable lymphocytic pleocytosis in children with ZIKV encephalitis. ZIKV encephalitis induced a selective encephalic but not systemic expression of cytokines. Abstract: Objective: To evaluate the clinical, laboratory, and immune characteristics of Zika virus (ZIKV)-associated encephalitis in pediatric patients after the epidemic in Huila, southern Colombia. Methods: A pediatric neuro-surveillance hospital study was conducted in a referral health center in southern Colombia, from October 2016 to October 2017. Cases of encephalitis were confirmed by nucleic acid amplification tests and serological methods in cerebrospinal fluid (CSF), plasma, and/or urine. Levels of six cytokines were evaluated by flow cytometry. Patients underwent daily clinical and laboratory follow-up. Results: Twenty children with probable encephalitis were included for further studies and 16 of them were confirmed. Four cases of bacterial meningoencephalitis ( Streptococcus pneumoniae, group B Streptococcus, Staphylococcus epidermidis, and Escherichia coli ) and 12 cases of viral encephalitis were identified, six of them associated with ZIKV infection. Other viral encephalitis cases were caused by herpes viruses ( n = 3), enterovirus ( n = 2), and dengue virus type 2 (DENV-2; n = 1) infections. ZIKV-associated encephalitis symptoms subsided faster than those of patients with encephalitis caused by other agents. CSF analysis revealed lymphocytic pleocytosis. Compared to healthy controls, children with ZIKV-associated encephalitis presented modest plasma interleukin (IL)-10 but not IL-2, IL-4, IL-6, interferon gamma (IFN-γ), or tumor necrosis factor alpha (TNF-α). Cytokine expression was differentially regulated, as dramatically elevated IL-6, IL-10, and IFN-γ levels were observed in CSF but not in paired plasma samples in one of the patients with ZIKV detectable in CSF. Conclusions: This study provides evidence that ZIKV is responsible for pediatric encephalitis in endemic areas, and the local presence of the virus may induce cephalic but not systemic expression of cytokines.